Development of an iatrogenic aneurysm nine months after pacemaker implantation: Consideration of causes and treatment. Issue 3 (September 2017) - Pak, Misun; Kagawa, Yuzo; Watanabe, Nobuhide; Imai, Kensuke; Endo, Akihiro; Tanabe, Kazuaki
Abstract: Careful technique is required in pacemaker implantation to avoid serious iatrogenic complications. A 70-year-old woman on an anticoagulant agent underwent pacemaker implantation. Nine months after implantation, a 35-mm pulsatile mass appeared just near the cranial edge of the generator. An iatrogenic pseudoaneurysm was suspected because ultrasonography showed communication with the blood stream through tiny artery. The resected mass proved to be a pseudoaneurysm. This was a rare case of iatrogenic delayed pseudoaneurysm appearing nine months later. It is essential to keep in mind the risk of pseudoaneurysm after pacemaker implantation, especially when the patient takes anticoagulant agents. <Learning objective: Iatrogenic delayed pseudoaneurysm might develop after pacemaker implantation. It is essential to avoid risk factors for a pseudoaneurysm after pacemaker implantation when the patient is taking anticoagulant agents and to keep in mind careful follow-up even after discharge. Prospective measures such as suspension of antithrombotic agents, minimizing puncture attempts, and wound compression are also important.>